Insights into uterine fluid proteins and putative roles on maternal recognition of pregnancy - Schmith, R A [UNESP]; Souza, F F [UNESP]; Camargo, L S [UNESP]; Guasti, P N [UNESP]; Canisso, I F; Codognoto, V M [UNESP]; Cavalero, T M [UNESP]; Meira, C [UNESP] (Elsevier, 2023)
The embryo is dependent on uterine secretions in early pregnancy and notably around the time of maternal recognition of pregnancy (MRP). This study aimed to identify key proteins in the uterine fluid and embryo before and around the time of MRP. We hypothesized that uterine fluid has a unique signature of proteins around the time of MRP. Mares were bred to a fertile stallion until ten embryos were obtained for each of days 7, 10 and12 post-ovulation. A gynecological tampon was inserted in utero for collection of the uterine fluid. Embryo flushing was carried out with Lactated Ringers Solution. Recovered embryos were flushed in DPBS, and then stored in DPBS enriched with proteinase inhibitors at -80°C. Uterine fluid was centrifuged, and the supernatant was stored at -80°C until analysis. The embryo was sonicated, centrifuged as the uterine fluid, and then stored at -80°C until analysis. Total protein was determined by the acid bicinchoninic method, in-gel tryptic digestion was carried out and samples were analyzed by mass-spectrometry (ESI-Q-TOF-MS/MS). Gene-ontology was carried out on a Panther, vs17.0. Multivariate-analyses based on principle component analysis (PCA), and partial least squares discriminant analysis-variables importance (PLS-DA/VIP) score were performed with Metaboanalyst, v5.0 via R-studio. The total protein numbers found at Days 7, 10, and 12 were 75, 81 and 84 in the uterine fluid and 151, 139, and 178 inthe embryos, respectively. The most abundant proteins (VIP-score, α>1.5) present in the embryos at Days 7, 10, and 12 were 0, 6 and 2; whereas uterine fluid had 0, 3 and 2 for the same respective days. Molecular functions found on gene-ontology were catalytic activity and binding in both samples from embryos and uterine fluids. There was a remarkable change in PCA from Day 7 to Day 10/12 in the embryo and uterine fluid proteins. Proteins found in great abundance in the embryos PLS-DA/VIP-score analysis were related to protection against thermal-stress, protein folding, stabilization, translation, lipid-metabolism and cell-structure. Cathepsin-B is involved with endometrial remodeling and implantation, but its role in the horse remains to be determined. Uterine fluid had proteins associated with the transport of molecules with low-molecular-weight; in the upregulation of the ERK1- and ERK2-cascades, which are essential for cell-proliferation, differentiation, adhesion, migration, survival; and calcium/phosphorus metabolism. Herein is the first description of Stanniocalcin-1 in equine embryos. In conclusion, the proteins found in utero may play a role in the MRP and the embryo proteins were related to mobility and protection functions. Acknowledgements: The Mass Spectrometry Facility at Brazilian Biosciences National Laboratory (LNBio), CNPEM, Campinas, Brazil is thanked for their support with the use of equipment.